Una mirada a nuevas masculinidades online. Análisis de discurso: el caso de Mr. Misterios, Machos Alfa, y la Manósfera - Albán Barreiro, Manuela (2024)
This essay analyzes the discourse of Mr. Misterios, a self-proclaimed “alpha male” who promotes the red pill philosophy on his YouTube channel. It is argued that this discourse emerges as a reaction to social changes that have empowered women, especially feminism and female sexual liberation, using Carol Pateman’s concept of the sexual contract (1995) as a theoretical basis. The red pill discourse is posited to go beyond traditional misogyny, becoming a “hostile sexism” that presents women as dangerous and socially powerful. Furthermore, Mr. Misterios is framed within the broader context of the manosphere, arguing that this type of online content serves as a pipeline to groups and forums with even more violent and radical rhetoric. In this sense, the essay seeks to account for the different concepts that characterize the discourse of the manosphere, such as female hypergamy, gynocentrism, and the red pill philosophy. It concludes by highlighting the need to pay attention to the mechanisms through which the manosphere spreads and normalizes sexist and aggressive discourses, taking advantage of the vulnerability of men who feel dissatisfied with their masculinity.